FAKTOR YANG BERHUBUNGAN DENGAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS TIPE 2 DI RSUD KOTA MAKASSAR TAHUN 2012 - Musdalifah Syamsul; Nurul Fatwa Abidin (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
Diabetes mellitus is one of the generative disease that increase every year. Most cases of diabetes mellitus in Indonesia is type 2, the prevalence 90-95% of all cases of diabetes. About 7% of South Sulawesi's population suffer from this disease. DM is a lifelong disease that requires good management, especially in terms of blood sugar control. The aim of study is to determine factors associated blood sugar level of patients DM type 2 in RSUD Kota Makassar.This study used cross sectional study approach and sample of 149 people. This research was conducted at Internal Polyclinic of RSUD Kota Makassar, data were collected using questionnaires and patient medical records file. The results of univariate analysis showed that most respondents got adequate family support (55.1%). Most people with type 2 diabetes melitus in RSUD Kota Makassar had good diet (51.5%). Blood sugar levels of respondents in this study which were still not well controlled (77.9%). Bivariate analysis with chi square test showed that family support was not related to blood sugar levels (p = 0.26) while diet was associated with blood sugar levels (p = 0,000, = 0.523). That blood sugar levels related with dietary, not family support. : It is desirable for health workers to optimize the counseling method for patients, especially in terms of motivating patients to control disease and family should be involved in the counseling activities.